Changes in bacterial loads, gas composition, volatile organic compounds, and glucosinolates of fresh bagged Ready-To-Eat rocket under different shelf life treatment scenarios - Yahya H.N.; Lignou S.; Wagstaff C.; Bell L. (Elsevier B.V., 2024)
Indexed by WOS/ Scopus